(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
In this research, we conclude that laser technology is one of the most important technologies today and in the future and has become at the forefront of the most important fields in all fields of science, because of its importance in improving products, treating diseases, and serving humanity in all areas of life, in addition to giving great hope for scientific revolutions. In the future in physics, chemistry, biology, engineering, etc. Therefore, it is necessary to work to take advantage of the distinct properties of laser materials in creating innovations and inventions that benefit humanity in the fields of peace, accelerating and facilitating life, in addition to getting rid of malignant diseases for which science today has not yet arrived at a radical cure, and many other services. Interest in this technology should increase so that it can From catching up with the scientific movement and unleashing the scientific energies and minds present in the country, proving their worth and competence